IMPLEMENTASI TEKNIK ANALISIS TEKNIKAL DALAM STRATEGI INVESTASI SAHAM DI PASAR BERKEMBANG - Yuliah, Yuliah; Triana, Leni (Yayasan Education and Social Center, 2024)
This research explores the application of technical analysis in stock investment strategies in emerging markets, focusing on unique characteristics such as high volatility and low liquidity. Technical analysis uses indicators such as Moving Average Convergence Divergence (MACD) and Relative Strength Index (RSI) to predict stock price movements. This study shows that although technical analysis can improve investment performance, its effectiveness is influenced by adjustments to local market conditions. Data was collected through in-depth interviews and participant observation in Southeast Asian stock markets. The findings show that adaptation of technical indicators and integration of modern technology, such as machine learning, can improve prediction accuracy. This research provides insights for investors to develop more effective investment strategies in emerging markets and emphasizes the importance of adapting technical analysis techniques to reflect specific market conditions